2020
DOI: 10.1371/journal.pone.0238019
|View full text |Cite
|
Sign up to set email alerts
|

The responsiveness of criminal networks to intentional attacks: Disrupting darknet drug trade

Abstract: Physical, technological, and social networks are often at risk of intentional attack. Despite the wide-spanning importance of network vulnerability, very little is known about how criminal networks respond to attacks or whether intentional attacks affect criminal activity in the long-run. To assess criminal network responsiveness, we designed an empirically-grounded agent-based simulation using population-level network data on 16,847 illicit drug exchanges between 7,295 users of an active darknet drug market a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…Targeted intervention efforts have already proven effective at reducing the frequency and severity of cybercrime incidents (Maimon et al, 2021). Large-scale attacks on the darknet ecosystem, for example, create distrust (Duxbury & Haynie, 2020) and lead to a reduction in the number of active vendors selling products (Chan et al, 2019). As such, viewing darknet markets as an interconnected network, and targeting markets that comprise a large portion of the ecosystem, should maximize the disruption effect of existent cybercrime intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted intervention efforts have already proven effective at reducing the frequency and severity of cybercrime incidents (Maimon et al, 2021). Large-scale attacks on the darknet ecosystem, for example, create distrust (Duxbury & Haynie, 2020) and lead to a reduction in the number of active vendors selling products (Chan et al, 2019). As such, viewing darknet markets as an interconnected network, and targeting markets that comprise a large portion of the ecosystem, should maximize the disruption effect of existent cybercrime intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…4 Choice paralysis is based on the idea that having an overabundance of options can cause individuals to complicate decision-making, resulting in higher levels of anxiety, indecision, and dissatisfaction (see Schwartz, 2014). 5 Identifying dependable measures of trust within the online illicit marketplace is inherently challenging since criminal network data are usually incomplete, thus requiring researchers to assume that the observed network is an adequate representation of the unmeasured criminal network (see Duxbury & Haynie, 2020). In the absence of complete trade records and transaction histories, extant research has relied on various metrics of criminal interaction that indirectly measure the mechanics of criminal behavior (Diviak er al., 2019;Papachristos & Smith, 2013).…”
Section: E N D N O T E Smentioning
confidence: 99%
“…Understanding the relationship between vendors' signaling behaviors and trust is important as it could assist law enforcement devise effective intervention strategies targeted at disrupting the online illicit marketplace (see Duxbury & Haynie, 2020;Holt et al, 2013). For instance, identifying the signaling mechanisms that convey trust in the online underground marketplace could help undercover law enforcement agents disguise themselves as credible sellers to both take down and apprehend serious market actors (see Jacobs, 1996aJacobs, , 1996b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The dark net (or dark web) is commonly used for illegal sales (drugs, weapons), organized crime offenses and money laundering or other economic crime offense (Bancroft, 2020). Duxbury and Haynie (2020) used SNA techniques on 16,847 illicit drug exchanges between 7295 users of an active dark net drug market to test for network robustness and vulnerability. They found that when networks are attacked, actors grow more cautious about forging ties, connecting less frequently and only to trustworthy alters.…”
Section: Network Enabling Criminal Activitiesmentioning
confidence: 99%